Essential oil bioactivity evaluation of the different populations of Cupressus against adult rice weevil (Sitophilus oryzae L.) - Mohammadreza Labbafi; Maryam Ahvazi; Farahnaz Khalighi-Sigaroodi; Hamideh Khalaj; Soolmaz Ahmadian; Fateme Tajabadi; Mousa Khani; Shahla Amini (Institue of Medicinal Plants, ACECR, 2021)
Background: A significant amount of crop production is destroyed annually by pests in the storage and significant damage is caused to crops. Recently, the use of essential oils as an alternative to pesticides in pest control has been considered. Due to the presence of α-pinene, Cupressus genus is a significant source of plant insecticides that can act as fumigant, repellency and inhibitory insecticides. Objective: The aim of this study was to investigate the insecticidal properties, repellency and nutritional parameters of essential oils of Cupressus species on Sitophilus oryzae in 2018. Methods: The experiment was conducted in a factorial arrangement based on completely randomized design with 4 replications. The essential oils of the different species and populations of Cupressus were prepared by the Clevenger apparatus using a water distillation method. The major constituents in the essential oils were analyzed by GC-MS and the biological effects of the essential oils against adult S. oryzae were investigated. Results: In the analysis of chemical compounds, α-pinene was identified as the main essential oils of the above species. The result showed that among the species, C. arizonica showed the highest Fumigant toxicity to S. oryzae with LC50 = 172.30 μl/L air. In investigating the effect of repellency on S. oryzae, essential oils of C. sempervirens L. var. horizontalis (France) with 80.61 % showed the highest distance. Conclusion: Due to the toxicity and high repellency effect of Cupressus essential oils on S. oryzae, this genus has high potential for use in storage pest control.